If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 40 = 12x + -40 Reorder the terms: 40 + 2x = 12x + -40 Reorder the terms: 40 + 2x = -40 + 12x Solving 40 + 2x = -40 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 40 + 2x + -12x = -40 + 12x + -12x Combine like terms: 2x + -12x = -10x 40 + -10x = -40 + 12x + -12x Combine like terms: 12x + -12x = 0 40 + -10x = -40 + 0 40 + -10x = -40 Add '-40' to each side of the equation. 40 + -40 + -10x = -40 + -40 Combine like terms: 40 + -40 = 0 0 + -10x = -40 + -40 -10x = -40 + -40 Combine like terms: -40 + -40 = -80 -10x = -80 Divide each side by '-10'. x = 8 Simplifying x = 8
| 5x-4=2x+6+x | | 37x=9x+4 | | 2(x-7)=10-4x | | 25x^2-15x-4=0 | | 12-6x=6x+34 | | 6x-10=46 | | 2+5+6rs= | | 2(y-6)-(y+2)=26 | | (x^2+16)(x^3-108)=0 | | 14a+12=84 | | 9[(4+4)-2]= | | .1(x^2+16)(x^3-108)=0 | | 4=5-3x | | -5(t-4)-7= | | 17=-5x-13 | | 6x+1=4x-3 | | 14=18-4x | | 1/9(p+18)+1/3(2p+3)=p+3 | | 2=-x-5 | | 13q-13q=22 | | (a-3)(1+7)-2=14 | | 3x-12x^2+x-12=0 | | -9+-6= | | a-3=-15 | | 3-2x(x-1)=x(3-2x)-(x-3) | | -2(r+7)=-35 | | x^100+x^2+1=0 | | -1/4(x-12)+1/2(x+2)=x+4 | | 2(x-3)=9 | | 65-2x=43x+15 | | -5=3m-13 | | 12-2(y+5)=4(y-7)-(y-1) |